Surgical resection for congenital lung malformation: Lessons learned from thoracotomy to biportal thoracoscopy under one-lung ventilation - Wan-Ting Hung; Yi-Chia Wang; Hsing-Hao Huang; Jui-Hung Tai; En-Ting Wu; Jin-Chung Shih; Wen-Ming Hsu (Journal of the Formosan Medical Association, 2022)
Background: The purpose of this study is to compare the clinical characteristics and surgical outcomes of thoracotomy and video-assisted thoracoscopic surgery (VATS) in children with congenital lung malformations (CLMs) in a tertiary referring center and to report our modified biportal VATS setting. Methods: This is a single-center retrospective chart review study including children who underwent surgical resection for CLMs between January 2007 and December 2020. Patient characteristics and surgical outcomes were compared between open and thoracoscopy, as well as conventional VATS and biportal VATS. Biportal setting included an anterior utility wound and a camera trocar wound with one-lung ventilation. Results: A total of 100 patients were identified. Twenty patients received thoracotomy, and 80 patients received VATS (67 conventional and 13 biportal VATS). The median age at operation was 0.4 months in the thoracotomy group and 4.7 months in the VATS group. More patients in the thoracotomy group had preoperative symptoms, comorbidities, and emergent operations. The patients who underwent thoracotomy had significantly longer postoperative ICU stays, chest tube durations, hospital stays, and more complications. The pathological analysis revealed 67 congenital pulmonary airway malformations, 27 pulmonary sequestration, 6 hybrid lesions, and one accompanying pleuropulmonary blastoma. Compared to conventional VATS, the ICU stay was shorter in the biportal VATS group, with comparable operative durations, hospital stay and complications. Conclusion: VATS for CLMs is associated with better postoperative recovery and fewer complications. Biportal VATS is also a safe and feasible approach.